THE PLACE AND ROLE OF THE MANAGING AUTHORITY FOR OPERATIONAL PROGRAM FOR FISHERIES AND MARITIME AFFAIRS (AM-POPAM) IN THE ABSORPTION OF EUROPEAN FUNDS FOR THE PERIOD 2014-2020 - Sebastian GUT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article analyzes the activity carried out by the Managing Authority for Operational Program for Fisheries and Maritime Affairs (POPAM) within the Directorate General of Fisheries (AM-POPAM) in order to ensure the information and implementation process on accessing European funds granted by POPAM for the period 2014- 2020 following the concluded contracts, measures implemented , the amounts that were allocated and the gain obtained by accessing them by the applicants as a result of the existing agreements between the European Community and Romania. The actions of DGP-AM-POPAM through its decision makers at central, regional and county level ensure information and communication, in accordance with the Regulation of Organization and Functioning of the Managing Authority for POPAM and the National Strategy of the Fisheries Sector for knowledge transfer for growth competitiveness and diversification and the need to modernize the fisheries sector, by processing and marketing fish products but also by developing markets by ensuring a wide and diversified range of products and services along with the use of renewable energy while protecting the environment. The methodology used consisted in studying the bibliographic sources, collecting, processing, analyzing and interpreting the data provided by the databases of DGP and MADR, as well as formulating conclusions on the status of projects submitted, amounts allocated, achievement of targets and measures that can be taken further to support fishing and aquaculture activities.